Wage Income Distribution and Mobility in Malta - Clemens Knoppe (Central Bank of Malta, 2018)
This paper uses information from a detailed administrative database on reported full-time employment incomes to study the distribution of wage incomes and mobility between 2000 and 2015 in Malta. Developments in wage distributions and mobility are discussed within the context of the structural changes that took place in the Maltese economy over the last decade. The main finding is that while inequality in Malta remains subdued by international standards, there has been an increase in recent years as low wages have remained stable in real terms, while those in the middle and at the top of the distribution have seen significant rises. Due to the rising demand for certain types of skills, wage mobility appears to have declined, particularly for older workers. This points to an importance of increased investment in education and retraining.
Keywords: D31; D63; J31; J62; J69; 330